Effect of the COVID-19 lockdown on orthopedic services in a tertiary hospital in Nepal - Sharma, Bishnu Dev; Sitaula, Jyoti; Neupane, Gaurav; Dawadi, Tej Prakash (Journal of Chitwan Medical College, 2021)
Background: The Corona virus disease (COVID-19) pandemic has been a global health crisis and has affected Nepal also. As a strategy to control the disease outbreak, the government of Nepal had introduced a four-month nationwide lockdown. This study aims to evaluate the impact of the national lockdown in orthopedic services in Chitwan Medical College. Methods: This cross-sectional analytical study included all the patients admitted and treated in the orthopedic department of Chitwan Medical College during lockdown period from 24 March to 21 July 2020, which was compared with the same four-month interval from 24 March to 21 July in 2019. Data collected included patient demographics, mechanism of injury, anatomical location, waiting time before surgery and hospital stay. Results: A total of 247 patients were treated during lockdown, with a reduction of 45.4% from 2019 (452 patients). Also, there was 39.1% (340 vs 207, p=0.009) reduction in trauma cases and 35.7% (347 vs 223, p=0.000) reduction in cases operated in lockdown. There was a decrease in pediatric patients during lockdown (p=0.044). Fall was the most common mechanism of injury in both groups (p=0.158) with decrease in road traffic accidents during lockdown 27.1% (n=56) vs 45% (n=153) in 2019 (p=0.000). The waiting time before surgery and hospital stay were also shortened (p=0.000). Conclusions: The impact of lockdown resulted in decreased number of orthopedic trauma admissions and cases operated. On such a crisis, only urgent and semi-urgent cases need to be managed while also protecting healthcare workers and patients